A monthly consumption indicator for Germany based on internet search query data - Torsten Schmidt; Simeon Vosen (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
In this study we introduce a new monthly indicator for private consumption in Germany based on search query time series provided by Google Trends. The indicator is based on unobserved factors extracted from a set of consumption-related search categories of the Google Trends application Insights for Search. The predictive performance of the indicator is assessed in real time relative to the European Commission's consumer confidence indicator and the European Commission's retail trade confidence indicator. In out-of-sample nowcasting experiments the Google indicator outperformed the surveybased indicators. In comparison to the other indicators, the new indicator also provided substantial predictive information on consumption beyond that already captured in other macroeconomic variables.
Keywords: C53; E21; E27; 330; Google Trends; Private Consumption; Forecasting; Consumer Sentiment Indicator